Today's Women in Terrorism - Verta Mega Arlinsa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The role of women in acts of terrorism is increasingly varied from just helping to hide terrorist escapees, intelligence activities even only being used by terrorist networks. This paper looks at the root of the problem in uncovering the increasingly diverse roots of terrorism radicalism. This article uses qualitative research methods with research variables namely terrorism ideology, women, and internet technology. The results of this study indicate that those who fall into this because of family factors and it is undeniable that family factors have a tremendous influence on the way of thinking and behaving in general, those who are members of this radical act of terrorism, their families have been one of the terrorists or terrorist accomplices. or understand radicalism after that environment, and information technology. In addition to the emptiness factor (lack of love, their presence is not accepted, while radical groups seem to accept it very well. And other factors are educational and economic factors, in this case they are terrorists who guarantee their daily needs provided they remain loyal and risking their lives to comply with all regulations.